Predictors of Posterior Fossa Syndrome: Results From an International Multicenter Cohort Study of Molecularly Characterized Medulloblastoma Patients. (1st September 2019) - Jabarkheel, Rashad; Amayiri, Nisreen; Yecies, Derek W; Huang, Yuhao; Toescu, Sebastian; Mabbott, Donald; Sudhakar, Sniya; Malik, Prateek; Laughlin, Suzanne; Chacko, Geeta; Mathew, Leni; Fisher, Paul; et al.
Abstract: INTRODUCTION: Posterior Fossa Syndrome (PFS) is a common complication following surgical resection of pediatric posterior fossa tumors. PFS is characterized by a combination of mutism, ataxia, and other behavioral symptoms that typically improves within weeks to months. Medulloblastoma histology, midline location, and brainstem invasion increase risk for PFS. Medulloblastoma subgroups have historically been treated as a single entity when assessing PFS risk, however, recent studies highlighting their clinical heterogeneity suggest the need for a subgroup-specific analysis of PFS risk. Here, we examine a large international multicenter cohort of molecularly characterized medulloblastoma patients to assess predictors of PFS. METHODS: We assembled a cohort of 270 medulloblastoma patients from 4 sites including Christian Medical College and Hospital (n = 87), Great Ormond Street Hospital (n = 25), Hospital for Sick Kids (n = 111), and Stanford University Medical Center (n = 47), who underwent surgical treatment of medulloblastoma and had molecular subgrouping of their tumors. Patient age at diagnosis, gender, tumor volume, and PFS status were assessed in addition to molecular subgroup. RESULTS: Overall, 25.9% of our cohort developed PFS. PFS patients were younger (mean difference −2.73 yr ± 0.8, P  = .0009) and had larger tumors (mean difference 16.99 cm3 ± 5.287, P  = .0015) that were more midline (OR = 20.03, P  < .0001). On multivariate analysis adjusting for age, sex, midline location, and tumor volume, WNT (adjusted OR = 5.19, P  = .022) and Group 4 (adjusted OR = 7.15, P  = .004) tumors were found to be independently associated with higher risk of PFS as compared to SHH tumors. CONCLUSION: Here, we present the largest molecularly characterized cohort of medulloblastoma patients in the context of PFS development. In combination with recent data showing that WNT and Group 4 tumors have a longer pre-diagnostic interval our results support the hypothesis that large midline tumors that grow slowly have a higher risk of PFS.